Modification of response reduction factors of overhead water tanks based on ductility factor - Pandian, Antony Vimal Paul (2024)
In the earthquake-resistant design of overhead tanks, this research dealt with the determination of the response reduction factor applicable to overhead water tanks performing beyond the elastic limit. Eight existing water tanks were selected for the investigation and 127 ground accelerations due to 10 Indian earthquakes were selected. The magnitude of the earthquakes selected ranges from 4.5 to 7.2. Initially, 10.16 million nonlinear dynamic data of response reduction factor had been produced using Newmark’s β method by varying parameters. From the results obtained, multi-linear regression analysis was made to arrive at the empirical formula relating the parameters and it was found that ductility factor was the most significant factor among others such as damping ratio, pre-post stiffness ratio, natural period, and soil types, in influencing response reduction factor. Eventually, It is concluded that the values of the response reduction factor to be adopted in the dynamic analysis of Overhead water tanks should be based on the desired value of the ductility factor.